2020
DOI: 10.1186/s12888-020-2433-8
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and risk assessment for anorexia nervosa in acute-care hospitals: a nationwide administrative database analysis

Abstract: Background: Anorexia nervosa (AN) is a common eating disorder with the highest mortality rate of all psychiatric diseases. However, few studies have examined inpatient characteristics and treatment for AN. This study aimed to characterise the association between mortality and risk factors in patients with AN in acute-care hospitals. Methods: We conducted a nationwide, retrospective analysis of the Japanese Diagnosis and Procedure Combination inpatient database. Data extraction occurred from April 2010 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…These lower SMRs in studies analyzing the mortality of patients with AN after hospitalization in psychiatric department may be explained by the fact that patients with AN hospitalized in these studies tend to be less severely malnourished and less clinically compromised than patients with AN hospitalized in our unit. Thus, mean BMI on admission was higher in these studies compared to our cohort: 14.5 kg/m 2 in the study published by Huas et al, 14 between 10.5 and 17.5 kg/m 2 in the study published by Rosling et al, 19 13.9 kg/m 2 for the deceased group in the study published by Fichter et al 14 And a lower BMI has been associated with a higher mortality in the literature 8,19,25,28 …”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…These lower SMRs in studies analyzing the mortality of patients with AN after hospitalization in psychiatric department may be explained by the fact that patients with AN hospitalized in these studies tend to be less severely malnourished and less clinically compromised than patients with AN hospitalized in our unit. Thus, mean BMI on admission was higher in these studies compared to our cohort: 14.5 kg/m 2 in the study published by Huas et al, 14 between 10.5 and 17.5 kg/m 2 in the study published by Rosling et al, 19 13.9 kg/m 2 for the deceased group in the study published by Fichter et al 14 And a lower BMI has been associated with a higher mortality in the literature 8,19,25,28 …”
Section: Discussionmentioning
confidence: 42%
“…However, mortality is even higher in tertiary care centers that treat the most severe forms of the disorder: SMR at 10.6 among adult inpatients in tertiary ED center 7 . Mortality rates in AN adults after an inpatient treatment have been largely studied 7‐33 . However, the results vary widely depending on the characteristics of the cohort studied (size, outpatient or inpatient, medical or psychiatric department, severity of malnutrition, duration of ED, duration of follow‐up), and on the methodology used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time period, there have been a few studies that have examined ED presentations among males. Among clinical ED samples, approximately 2.1–5.2% of patients are estimated to be males (Edakubo & Fushimi, 2020; Harada et al, 2016; Nakai et al, 2001; Nakai et al, 2018). While researchers have not identified any significant differences in clinical features between male and female patients with AN (Harada et al, 2016), male patients have a higher mortality rate than their female counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…While researchers have not identified any significant differences in clinical features between male and female patients with AN (Harada et al, 2016), male patients have a higher mortality rate than their female counterparts. For instance, Edakubo and Fushimi (2020) assessed a mixed‐gender sample of patients with AN in acute hospital settings, and found that the adjusted odds ratio of mortality for male patients was two times greater than female patients with AN.…”
Section: Resultsmentioning
confidence: 99%